MENINGKATKAN KUALITAS PENDIDIKAN UNTUK ANAK DENGAN BERKEBUTUHAN KHUSUS TUNA RUNGU DAN WICARA DI SLB B DI ERA PANDEMI - Puguh Setyo Nugroho; Nyilo Purnami; Rosa Falerina; Rizka Fathoni Perdana; Yoga Rahmadiyanto; Chriscelia Valery So (Universitas Airlangga, 2021)
AbstractA child with a hearing and speech impairment has the same right to education as all children. An equal access to education as an investment to their future. The Acceleration of Digitization and restrictions on activities that occurred during the pandemic and the fourth industrial revolution have led to a challenge of education process, especially for hearing and speech impairments students. This cross-sectional study aims to discover the quality of education and evaluate the knowledge gained from participating in an educational course by giving pre-test and post-test questionnaire. A polling method was conducted to assess the participants' attitudes and psychomotor. This study was attended by 627 respondents including SLB B teachers 267 respondents (43%), parents of students 191 respondents (30%) and the public 169 respondents (27%). The average pre-test score was 47,67 (+15,69) and the post-test average was 80,67 (+22,73). A mean difference between pretest and post-test score was significant at p < 0.0001. The principles of the education for a child with a hearing and speech impairment is to building children's independence by 293 respondents (23%), using innovative methods of teaching 143 respondents (20%) and increase the utilization of educational facilities and infrastructure 64 respondents (10%). The strategies to teach a child with a hearing and speech impairment is using innovative methods, starting with understand the children’s character and needs. One of the keys to a successful academic experience for children with disabilities is a productive and supportive relationship between parents and teachers.Keywords : Hearing impairment, speech impairment, educational, independence AbstrakAnak dengan tuna rungu dan wicara memiliki hak dasar. Salah satu hak dasar adalah mendapatkan akses pendidikan yang berkualitas untuk memberikan bekal untuk kehidupan masa depan. Pandemi, revolusi industri 4.0 terjadi percepatan digitalisasi informasi yang terjadi dan pembatasan fisik menjadi tantangan terhadap proses pendidikan untuk anak tuna rungu dan wicara. Studi cross sectional untuk menilai kualitas dan upaya peningkatan kualitas pendidikan dilaksanakan dengan seminar pendidikan dan dilakukan pre test sebelum kegiatan dan post test setelah kegiatan untuk menilai peningkatan pengetahuan. Survei jajak pendapat dilakukan untuk menilai sikap dan psikomotor peserta. Studi ini diikuti oleh 627 responden meliputi guru SLB B 267 orang (43 %), orang tua anak didik191 orang (30 %) dan masyarakat umum 169 orang (27 %). Aspek pengetahuan didapatkan hasil pre test 47,67 (+15,69). Hasil rata rata post test 80,67 (+22,73). Perbandingan hasil pre test dan post test didapatkan hasil yang berbeda signifikan (p<0,0001) sehingga didapatkan peningkatan pengetahuan sebelum dan setelah kegiatan. Sedangkan fokus pendidikan untuk anak tuna rungu dan wicara adalah menumbuhkan kemandirian anak di masa depan 293 orang (47 %), inovasi metode pembelajaran 143 orang (23 %), 127 orang (20 %) dan Penguatan sarana dan prasarana pembelajaran 64 orang (10 %). Perlu inovasi dalam metode pendidikan untuk anak tuna rungu dan tuna wicara. Inovasi dimulai dengan memahami karakter dan kebutuhan anak tuna rungu dan wicara. Kolaborasi antara segenap elemen orang tua dan guru menjadi kunci keberhasilan pendidikan untuk anak tuna rungu dan tuna wicara yang bertujuan untuk kemandirian dan bekal di masa depanKata kunci : Tuna rungu dan tuna wicara, pendidikan, kemandirian